Time-stable wetting effect of plasma-treated biodegradable scaffolds functionalized with graphene oxide - Lipovka A. A. Anna Anatolyevna; Rodriguez (Rodriges) Contreras R. D. Raul David; Bolbasov E. N. Evgeny Nikolaevich; Marjin (Maryin) P. V. Pavel Vladimirovich; Tverdokhlebov S. I. Sergei Ivanovich; Sheremet E. S. Evgeniya Sergeevna (2020, 2020)
Title screen